2008
DOI: 10.1055/s-2008-1072789
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bispyrrolidines by Radical Cyclisation of Diallylamines Using Phosphorus Hydrides

Abstract: Sequential radical addition-cyclisation reactions of diallylamines using either hypophosphorous acid or a bisphosphinothioate are shown to afford bispyrrolidines in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Parson and Wright designed a nice reaction sequence for the reaction of phosphinic acid or phosphinothionic acid with diallylamines. The initial radical generated reacted with a diallylamine to form intermediate 381 which underwent second radical reaction with another diallylamine to afford bispyrrolidines 382 264. The Montchamp group also demonstrated that hydrophosphonyl radical can add to the same carbon of alkyne twice to form 1,1-bis-H-phosphinate 383.Scheme 162A limited literature information was found on the reactions of alkyl-or arylphosphonyl radicals [(RO)RP(O)•].…”
mentioning
confidence: 97%
“…Parson and Wright designed a nice reaction sequence for the reaction of phosphinic acid or phosphinothionic acid with diallylamines. The initial radical generated reacted with a diallylamine to form intermediate 381 which underwent second radical reaction with another diallylamine to afford bispyrrolidines 382 264. The Montchamp group also demonstrated that hydrophosphonyl radical can add to the same carbon of alkyne twice to form 1,1-bis-H-phosphinate 383.Scheme 162A limited literature information was found on the reactions of alkyl-or arylphosphonyl radicals [(RO)RP(O)•].…”
mentioning
confidence: 97%
“…The phosphorus‐centered radical [HPO 2 − ]• was detected in these studies. There is much work presenting reactions, in which hypophosphites, including sodium hypophosphite, act as a radical‐chain carrier . There are also data indicating that the first coating layer on the substrates having aluminum or iron appears via the exchange reaction : trueright Fe + Ni 2+ Fe 2++ Ni trueright2 Al +3 Ni 2+2 Al 3++3 Ni …”
Section: Literature Hypotheses Of the Ni‐p Coating Deposition Mechanismmentioning
confidence: 99%
“…Their highly efficient addition reactions to alkenes have been achieved with transition metal catalysts [22][23][24]. A radical reaction involving phosphorus-centered radicals generated in situ is a classical method for P-C bond formation [25][26][27][28][29][30]; however, the use of primary phosphines and phosphine oxides in a radical reaction is relatively rare compared to that of secondary phosphines and phosphine oxides [31][32][33][34][35][36][37][38]. The stereochemistry on a phosphorus atom has not received much attention, despite the fact that the introduction of at least three different substituents to the phosphorus atom gives rise to the stereogenic center on the phosphorus atom.…”
Section: Introductionmentioning
confidence: 99%